EQUILIBRIUM COMPOSITIONS OF COEXISTING GARNET AND ORTHOPYROXENE: EXPERIMENTAL DETERMINATIONS IN THE SYSTEM FEO-MGO-AL2O3-SIO2, AND APPLICATIONS - Lee Han Yeang; Ganguly Jibamitra (My University, 1988)
We have determined the Fe-Mg fractionation between coexisting garnet and orthopyroxene at 20–45 kb, 975–1400 C, and the effect of iron on alumina solubility in orthopyroxene at 25 kb, 1200 C, and 20 kb, 975 C in the FMAS system. The equilibrium compositions were constrained by experiments with crystalline starting mixtures of garnet and orthopyroxene of known initial compositions in graphite capsules. All iron was assumed to be Fe2+. A mixture of PbO with about 55 mol per cent PbF2 proved very effective as a flux. The experimental results do not suggest any significant dependence of KD on Fe/Mg ratio at T 1000 C. The lnKD vs. l/T data have been treated in terms of both linear and non-linear thermodynamic functional forms, and combined with the garnet mixing model of Ganguly and Saxena (1984) to develop geothermometric expressions relating temperature to KD and Ca and Mn concentrations in garnet. The effect of Fe is similar to that of Ca and Cr3+ in reducing the alumina solubility in orthopyroxene in equilibrium with garnet relative to that in the MAS system. Thus, the direct application of the alumina solubility data in the MAS system to natural assemblages could lead to significant overestimation of pressure, probably by about 5 kb for the relatively common garnetlherzolites with about 25 mol per cent Ca+Fe2+ in garnet and about 1 wt. per cent Al2O3 in orthopyroxene.